Clinical Study of Phospholipase D1 and Choline Kinase Alpha Enzymes in Women with Breast Cancer in Thi-Qar Governorate-Iraq - Husam Mohammed Kredy (Journal of Global Pharma Technology, 2019)
Objective: Breast cancer is the most common cancer among women, comprising 18% of all female cancers, and worldwide, breast cancer is the fifth most common cause of cancer mortality. The study was designed to determine and compare the levels of phospholipase D1 (PLD1) and choline kinase alpha (CHKAα) enzymes in Breast cancer patients and apparently healthy individuals.  Material and Methods: Blood phospholipase D1 (PLD1) and choline kinase alpha (CHKAα) enzymes levels were determined in 85 breast cancer patients and 55 apparently healthy subjects. Histopathological and immunohistochemical analysis done for (50) cases (out of those 85 breast cancer patients), tissue samples are collected from patients with breast cancer who undergoing surgical resection (mastectomy) and normal breast tissues: (control group, which include normal breast tissue from patients with benign lesions, and normal breast tissue from the same women with breast cancer). Results: The levels of serum phospholipase D1 (PLD1) and choline kinase alpha (CHKAα) enzymes were showing significant increase in breast cancer patients as compared to control group (P ≤ 0.05). We found that 82% of breast cancer biopsies were phospholipase D1 positive. There was no expression of phospholipase D1   in all normal breast tissues. Sixty-seven percent of breast cancer biopsies were choline kinase alpha positive. There was no expression of choline kinase alpha in all normal breast tissues. Conclusion: In Breast cancer patients, we found that there is an increase in (PLD1) and (CHKAα) enzymes level both in serum and malignant tissue, and this suggests that the overexpression of PLD1 and CHKAα may play an important role in the human breast tumorigenesis and they are useful markers for breast cancer.Keywords: Breast cancer, Phospholipids, Phospholipase D1 (PLD1), Choline kinase alpha (CHKAα).